Adaptive Secure Rate Allocation via TAS/MRC under Multi-Antenna Eavesdroppers - Muhammad, Irfan; Lopez, Onel L. Alcaraz; Alves, Hirley; Osorio, Diana P. M.; Olivo, Edgar E. Benitez [UNESP]; Latva-aho, Matti; IEEE (Ieee, 2019)
This paper investigates the secrecy outage performance of a multiple-input multiple-output and multi-antenna eavesdropper system. We consider a novel formulation for the secrecy outage probability, which is capable of quantifying reliability and secrecy separately, thus constituting a useful tool in the context of new scenarios with stringent requirements on reliability as the case of ultra-reliable low-latency communication. Our system considers a multi-antenna transmitter, Alice, that employs transmit antenna selection, a legitimate multi-antenna receiver, Bob, and a multi-antenna eavesdropper, Eve, where both employing maximal-ratio combining. For this system, exact and simpler asymptotic closed-form expressions for the conditional outage probability are provided. Moreover, for the case where channel state information is available at the three nodes, a numerical secure throughput maximization is carried out by considering quality-of-service and security constraints for an adaptive rate allocation scheme in an ON-OFF transmission. Our proposed closed-form expressions are validated via Monte Carlo simulations.